Chemical vapor transport reactions - Binnewies, Michael (Walter de Gruyter, 2012)
This comprehensive handbook covers the diverse aspects of chemical vapor transport reactions from basic research to important practical applications. The book begins with an overview of models for chemical vapor transport reactions and then proceeds to treat the specific chemical transport reactions for the elements, halides, oxides, sulfides, selenides, tellurides, pnictides, among others. Aspects of transport from intermetallic phases, the stability of gas particles, thermodynamic data, modeling software and laboratory techniques are also covered. Selected experiments using chemical vapor transport reactions round out the work, making this book a useful reference for researchers and instructors in solid state and inorganic chemistry.